Tinjauan pemungutan retribusi parkir di tepi jalan umum kota Makassar - Triratnawati Triratnawati; Sri Nirmala Sari; Mahardian Hersanti Paramita (Income Journal: Accounting, Management and Economic Research, 2022)
The purpose of the research will be conducted is to see the suitability of collection of Parking Levies based on Makassar City Regional Regulation number 17 of 2006 on management of public curb parking in Makassar City Region. The type of data used in this study is qualitative data. Sources of data used in this study are primary data and secondary data. The results of research indicate that the collection of parking fees implemented fairly well can be seen from the collection of parking fees made by collectors to the parking attendant is in accordance with the agreement made by PD Parking Makassar Raya